Influence of Mothers/Grandmothers Coviewing Cartoons With Children on Children’s Viewing Experience - Meng, Qi; Sheng, Xiaoying; Zhao, Jiayin; Wang, Yifang; Su, Zhuqing (Frontiers in Psychology, 2020)
Watching cartoons is one important event in children’s early lives. This activity is highly influential on many factors, such as children’s cognitive and behavioral development. Some researchers believe that parents should coview cartoons with children to help them filter and distinguish useful content. However, intergenerational education is already common in China, and the influence of grandparents cannot be ignored. Because they are in different stages of life, the members of these two generations manifest great differences in parenting style, which may lead to differences in child development. Does this generational difference have differential effects on the children’s cartoon-viewing experience? We recruited 89 parents and grandparents and their kindergarten-aged children (approximately 5 years old) to participate in the study. The mothers or grandmothers were asked to coview a cartoon for approximately 7 minutes with their child, after which the child was asked questions about the cartoon-viewing experience. The results show the following. (1) Compared with grandmothers, mothers generally think that cartoons have a very high influence on children’s physical and mental health (X² =8.83, p<0.05). (2) Mothers place more restrictions on the content of cartoons that their children view, whereas grandmothers’ attitudes are characterized by greater tolerance (X² =11.94, p<0.01). (3) In the case of coviewing with mothers, when the children are asked “why” questions about the cartoon-viewing experience questionnaire, they use more experience proofs to explain their answers than when they coview with grandmothers (X² =16.69, p<0.01; X² =10.44, p<0.05).